Image compression-encryption algorithms by combining hyper-chaotic system with discrete fractional random transform. (July 2018) - Gong, Lihua; Deng, Chengzhi; Pan, Shumin; Zhou, Nanrun
Highlights: A simultaneous image encryption-compression scheme based on hyper-chaotic system and DFrRT is proposed. The original image is transformed into a spectrum by DCT and the spectrum is compressed by spectrum cutting. The algorithm can compress and encrypt multiple images by using Zigzag scanning. Abstract: Based on hyper-chaotic system and discrete fractional random transform, an image compression-encryption algorithm is designed. The original image is first transformed into a spectrum by the discrete cosine transform and the resulting spectrum is compressed according to the method of spectrum cutting. The random matrix of the discrete fractional random transform is controlled by a chaotic sequence originated from the high dimensional hyper-chaotic system. Then the compressed spectrum is encrypted by the discrete fractional random transform. The order of DFrRT and the parameters of the hyper-chaotic system are the main keys of this image compression and encryption algorithm. The proposed algorithm can compress and encrypt image signal, especially can encrypt multiple images once. To achieve the compression of multiple images, the images are transformed into spectra by the discrete cosine transform, and then the spectra are incised and spliced into a composite spectrum by Zigzag scanning. Simulation results demonstrate that the proposed image compression and encryption algorithm is of high security and good compression performance.